2021
DOI: 10.1111/mec.15924
|View full text |Cite
|
Sign up to set email alerts
|

Volcanism and palaeoclimate change drive diversification of the world's largest whip spider (Amblypygi)

Abstract: The tropics contain many of the most biodiverse regions on Earth but the processes responsible for generating this diversity remain poorly understood. This study investigated the drivers of diversification in arthropods with stenotopic ecological requirements and limited dispersal capability using as a model the monotypic whip spider (Amblypygi) genus Acanthophrynus, widespread in the tropical deciduous forests of Mexico. We hypothesized that for these organisms, the tropical deciduous forests serve as a condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 123 publications
0
13
0
Order By: Relevance
“…The Earth’s complex topographical history often generates opportunities for population isolation and differentiation ( Yan et al, 2010 ; Hou et al, 2014 ; Wang et al, 2021 ), especially for montane species. Mountain-building is often associated with tectonic forces, promoting population divergence through vicariance ( Hoorn et al, 2010 ; Smith et al, 2014 ; Simões et al, 2016 ; Schramm et al, 2021 ). However, previous studies suggested that mountain building might not be regarded as the sole driver in the diversification of montane species ( Kong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Earth’s complex topographical history often generates opportunities for population isolation and differentiation ( Yan et al, 2010 ; Hou et al, 2014 ; Wang et al, 2021 ), especially for montane species. Mountain-building is often associated with tectonic forces, promoting population divergence through vicariance ( Hoorn et al, 2010 ; Smith et al, 2014 ; Simões et al, 2016 ; Schramm et al, 2021 ). However, previous studies suggested that mountain building might not be regarded as the sole driver in the diversification of montane species ( Kong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the old age of many arachnid lineages, empirical studies have helped to reconstruct past events as old as the breakups of Pangea and Gondwana (Boyer et al, 2007;Rix and Harvey, 2012;Xu et al, 2015;Clouse et al, 2017;Chousou-Polydouri et al, 2018) and diversification on major land masses (Chamberland et al, 2018;Esposito and Prendini, 2019;Turk et al, 2020;Ledford et al, 2021;Turk et al, 2021b). Arachnids have featured in research of evolutionary consequences of global climatic oscillations (Luo et al, 2020) and, at finer geographical scales, of glaciation events (Xu et al, 2016;Santibañez-Loṕez et al, 2021), tectonic movements (Opatova et al, 2016), formation of rivers and mountain chains (Hedin et al, 2013;Emata and Hedin, 2016;Xu et al, 2018;Schramm et al, 2021), aridification (Abrams et al, 2019), and other biotic/abiotic events (Bond et al, 2020) as well as processes involved with subterranean colonization and diversification (Harms et al, 2018). Island biogeography has extensively utilized arachnids in empirical and synthetic research bearing on the formation of, and diversification on, island archipelagos such as Hawaii (Gillespie, 2002), the Caribbean (C ̌andek et al, 2019;Pfingstl et al, 2019;Crews and Esposito, 2020;Shapiro et al, 2022), the Indian Ocean islands (Agnarsson and Kuntner, 2012), or the Malay archipelago (Turk et al, 2021a;Silva De Miranda et al, 2022).…”
Section: Arachnids As Biogeographical Model Organismsmentioning
confidence: 99%
“…The active volcanism, high biodiversity and relatively stable Pleistocene climate in Changbai Mts make it an ideal place for testing the species pump and species attractor hypotheses. Previous studies mostly focused on terrestrial species (Fjeldsa, 2006; Schramm et al, 2021; Sedano & Burns, 2010), but freshwater animals might be different from them in biogeography and distributions (Malicky, 1983). Given that rivers are dendritic networks, freshwater animals can disperse through these branches only when branches are fully or temporarily connected by suitable habitat (Inoue & Berg, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The “species pumps” hypothesis is well illustrated by Neotropical tanager birds, in which the uplifts of the Northern Andes as species pumps drove the early burst of diversification and subsequence dispersals out of the Northern Andes (Esquerré et al, 2019; Fjeldsa, 2006; Sedano & Burns, 2010). Species pumps associated with volcanic activities have also been inferred for the diversification of whip spiders across the Trans‐Mexican Volcanic Belt (Schramm et al, 2021). On the contrary, volcanos or tectonic activities might serve as “species attractor” for attracting species from adjacent areas to occupy the newly generated ecological niches, as proved by butterfly and glassfrogs with multiple colonizations of the Andes from lowlands (Chazot et al, 2016; Hutter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation